2020
DOI: 10.5194/hess-24-697-2020
|View full text |Cite
|
Sign up to set email alerts
|

Multimodel simulation of vertical gas transfer in a temperate lake

Abstract: Abstract. In recent decades, several lake models of varying complexity have been developed and incorporated into numerical weather prediction systems and climate models. To foster enhanced forecasting ability and verification, improvement of these lake models remains essential. This especially applies to the limited simulation capabilities of biogeochemical processes in lakes and greenhouse gas exchanges with the atmosphere. Here we present multi-model simulations of physical variables and dissolved gas dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…The average parameter uncertainty was 2.10°C and 1.86°C for epilimnion and full-profile temperature simulations, respectively ( Figure S3). The model generally performed better in predicting the full-profile temperature than the epilimnion temperature, consistent with our previous assessment on a temperate lake (Guseva et al, 2020).…”
Section: Model Performancesupporting
confidence: 89%
See 1 more Smart Citation
“…The average parameter uncertainty was 2.10°C and 1.86°C for epilimnion and full-profile temperature simulations, respectively ( Figure S3). The model generally performed better in predicting the full-profile temperature than the epilimnion temperature, consistent with our previous assessment on a temperate lake (Guseva et al, 2020).…”
Section: Model Performancesupporting
confidence: 89%
“…As such, improving the capability of 1-D lake models in representing the thermal regimes of diverse lake systems is of great value. Previous lake model validations mostly focused on individual lakes because data for calibration and verification of a large variety of lakes are not readily available (Guseva et al, 2020;Stepanenko et al, 2010). Also, previous studies did not identify which parameters or model processes should be the focus for improving model performance at the global scale, making it difficult to determine whether the developed numerical treatments are appropriate for regional or global applications is unclear.…”
mentioning
confidence: 99%
“…These multi-model ensembles offer the oppor-tunity to inter-compare models for an improved understanding of process representation and inter-model differences as well as for model improvement. Some MIPs examples include FireMIP for the fire regime and its drivers (Rabin et al, 2017); CMIP for past, present, and future climate changes and their drivers (Eyring et al, 2016;Kageyama et al, 2018); LakeMIP for physical and biogeochemical processes of lakes (Stepanenko et al, 2010;Thiery et al, 2014); AgMIP for crop growth (Rosenzweig et al, 2013); and WaterMIP or ISIMIP for the water cycle (Haddeland et al, 2011;Frieler et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, MIPs have underlined the need to go beyond good overall model performance and to improve process representation in the models (Guseva et al, 2020), integrate missing processes (Friend et al, 2014), and reduce uncertainties (Warszawski et al, 2014). MIPs showed that robust similarities exist among models, and as a result models are not strictly independent of each other given previous and legacy versions, and there are existing links among modelling communities who indirectly transfer some models' strengths and weaknesses by sharing their ideas and codes (Masson and Knutti, 2011;Knutti et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A large variety of different numerical models have been used for simulating temperature and hydrodynamics in lakes and reservoirs, as well as the biogeochemical and ecological processes that depend on it (e.g. Dissanayake et al, 2019;Guseva et al, 2020;Wang et al, 2020;Xu et al, 2021). While the mechanistic description of underlying physical processes is identical or at least similar in all models, they differ in their dimensionality, i.e.…”
Section: Introductionmentioning
confidence: 99%